2012
DOI: 10.1080/09637494.2011.644085
|View full text |Cite
|
Sign up to set email alerts
|

Megachurches and the Problem of Leadership: an Analysis of the Encounter between the Evangelical World and Politics in Argentina

Abstract: Researchers usually address the political aspect of Evangelical groups by highlighting their involvement in party politics: their ability to create new organisations or form alliances with existing ones, introducing into the electoral field the assumption of a more or less homogeneous or easily influenced 'Christian vote'. However, historical experience in Argentina shows that launching into politics is full of obstacles. Some of the most important innovations introduced by Neo-Pentecostalism -as the fastest-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The discipline that cell groups promote, as well as the leadership that is exercised at the internal level of the group, added to the training that the network provides, are spaces where habits of thought and behavior are forged (Reu 2019), producing some form of Christian citizenship that transforms contemplation into action. Regarding the role of evangelicals in Argentine politics, Algranti (2012) suggested that the most important impact of megachurches was at the level of the small groups, where cell leaders can encourage their disciples to participate in the political scene, beginning at the local or municipal level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discipline that cell groups promote, as well as the leadership that is exercised at the internal level of the group, added to the training that the network provides, are spaces where habits of thought and behavior are forged (Reu 2019), producing some form of Christian citizenship that transforms contemplation into action. Regarding the role of evangelicals in Argentine politics, Algranti (2012) suggested that the most important impact of megachurches was at the level of the small groups, where cell leaders can encourage their disciples to participate in the political scene, beginning at the local or municipal level.…”
Section: Discussionmentioning
confidence: 99%
“…O'Neill (2010, p. 62), describes the cell groups of the Guatemalan megachurch El Shaddai as a combination of "classroom, self-help group, and emotional laboratory" where a form of Christian citizenship is developed, a place where contemplation becomes action. Other authors have observed that the discipline that the cell groups promote, help megachurch pastors to mobilize believers to participate in national politics (Reu, 2019) (Algranti, 2012). For example, in Alas de Águila church in Altos de Chiapas (Mexico), through a transformation of the G-12 model, pastor Esdras Alonso, created the Army of God, a kind of elite squad with military ranks, whose function is to actively participate in the regional and national politics (Feria Arroyo 2017).…”
Section: Theologies Of Growth: Prosperity Wealth Transfer and Dominionmentioning
confidence: 99%
“…Such engagement has led to the creation of political parties in Colombia, Venezuela and Nicaragua in particular (Kim and Kim 2008: 169), and varying degrees of electoral success in Argentina and Brazil (Wilson 2011: 26), but it is at least arguably the case that ultimately such engagement has proven problematic for the megachurches. Algranti (2012) argues that for all their influence on their members, the Argentinian megachurches have singularly failed to shape national political life, and, indeed, that their leadership has become better trained, better qualified and better able to present themselves on the public stage and develop their own platform, they have distanced themselves from the community that they lead, resulting in a fair measure of conflict between church leaders and Evangelical politicians who both claim to speak for the community that neither groups now adequately reflect. This has led to a desire for churches to build influence in all spheres of society and encourage their members to engage with public life in all its fullness and aspire to leadership opportunities in other fields.…”
Section: Megachurches' Political Engagement and Cultural Influencementioning
confidence: 99%
“…On the one hand, as stated above, the governability crisis of the life in confinement conditions. On the other hand, at a strictly religious level, this is a time of strong expansion of Neo-Pentecostalism in the Argentine society, through public campaigns (Wynarczyk, 2009: 261–323), the proliferation of small churches (Semán, 2010: 26–32) and others that would eventually turn into megachurches (Algranti, 2012: 61–65), their outreach activities to youth (Mosqueira, 2014: 33–63), and their territorial policy (Carbonelli, 2012: 90–122). The growth of Evangelicals was statistically recorded in 2008 as approximately 9% of the Argentine population in the context of a Catholic majority (76.5%), and a share who are indifferent to religious ideas (11.3%) (Mallimaci et al, 2015: 255–260).…”
Section: Periodization: From the First Prison Blocks To Unit 25mentioning
confidence: 99%